2016
DOI: 10.1111/echo.13232
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Limitations of Current Adult Nomograms for the Aorta Obtained by Noninvasive Cardiovascular Imaging

Abstract: Normalized measurements for the evaluation of aortic disease severity are preferred to the adoption of generic cutoff values. The purpose of this review is to evaluate the strengths and limitations of currently available aortic nomograms by echocardiography, computed tomography (CT), and magnetic resonance imaging (MRI). A literature search was conducted accessing the National Library of Medicine using the keywords normal values, aorta, echocardiography, CT, and MRI. Addition of these keywords further refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
(531 reference statements)
1
16
0
Order By: Relevance
“…Although the difference in mean aortic diameter between the age group of 55–65 years and ≥75 years was only 1 mm for both the ascending and descending aorta, the aortic diameter above 55 years still increased. Our results show the 95th percentile for persons above the age of 75 years old to be 43 mm for ascending and 35 mm for descending aorta for men and 41 mm and 33 for women, an age group for whom distribution data are currently scarce 11. Our data further establish the range of thoracic aortic diameters, which is similar to data found in a study performed in Germany 16.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the difference in mean aortic diameter between the age group of 55–65 years and ≥75 years was only 1 mm for both the ascending and descending aorta, the aortic diameter above 55 years still increased. Our results show the 95th percentile for persons above the age of 75 years old to be 43 mm for ascending and 35 mm for descending aorta for men and 41 mm and 33 for women, an age group for whom distribution data are currently scarce 11. Our data further establish the range of thoracic aortic diameters, which is similar to data found in a study performed in Germany 16.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, this threshold of 40 mm6 may not be directly applicable to older individuals, especially given increasing evidence suggesting that aortic diameters change with age 7–9. Together with the finding that aortic complications mostly occur at older age,10 this emphasizes the need for data on the distribution of aortic diameters among older persons 11…”
Section: Introductionmentioning
confidence: 99%
“…These adult nomograms have some limitations: small sample size, poorly defined 'normal' subjects, bias to BSA (which is adversely affected by obesity), and finally a sharp jump in results when the subject turns 40 owing to a change in the equation used. These problems have been well described elsewhere (65).…”
Section: Rationale and Discussionmentioning
confidence: 91%
“…RA diameters (15), RV long-axis diameter (15,22), and RV mass (15) increase with age, while data on the RV area were contrasting, with a study reporting a slight increase (21) and other a decrease of the RV area (18). Some studies (15,18,22,27) showed significant relations of cardiac measurements with gender. All chambers diameters, volumes and the LV mass were higher in men (15,18,21,22), even after correction for BSA (18), as well as great arteries (15,22,27).…”
Section: Correlation Of Cardiac Measurements With Age and Gender And mentioning
confidence: 99%
“…Some studies (15,18,22,27) showed significant relations of cardiac measurements with gender. All chambers diameters, volumes and the LV mass were higher in men (15,18,21,22), even after correction for BSA (18), as well as great arteries (15,22,27). BSA correction however mitigated RA diameters and RA volume differences among gender and eliminated differences in LA volume (18).…”
Section: Correlation Of Cardiac Measurements With Age and Gender And mentioning
confidence: 99%